Strategy for Enforcing the Law for Solving the Extinction Problem of Siamese Rosewood - ไชยเดือน, คมเดช (Journal for Developing the Social and Community, 2016)
Siamese Rosewood is natural tree, originated in Cambodia, Vietnam, Laos and Thailand, but now, is prone to extinction. In the past, Chinese people used to build palace because believed that Siamese Rosewood is sacred wood that should be occupied, in addition, wood is also used for making the furniture and other products because the wood is beautifully designed and durable. This is cause to illegally cut rosewood widely. However, Thailand signed the CITES treaty on International Trade concerning types of wildlife and wild plants that are close to extinction (The Convention on International Trade in Endangered Species of Wild Fauna and Flora) as result to issue an additional punishment for offender. Although the government has increased the offense, the wood is still heavily threatened and high risk of extinction. Therefore, the